Reproducibility of maximum isokinetic trunk strength testing in healthy adolescent athletes - Müller, J.; Müller, S.; Stoll. J.; Fröhlich, K.; Baur, H.; Mayer, F. (Sport-Orthopädie - Sport-Traumatologie, 2014)
Hintergrund